Altered Composition of the Oral Microbiota in Depression Among Cigarette Smokers: A Pilot Study - Al Bataineh, Mohammad Tahseen; Künstner, Axel; Dash, Nihar Ranjan; Abdulsalam, Rushud Mahmood; Al-Kayyali, Rafla Zaid Ali; Adi, M. Besher; Alsafar, Habiba S.; Busch, Hauke; Ibrahim, Saleh Mohamed (Frontiers in Psychiatry, 2022)
Alterations in the oral microbiota composition may influence mental health. However, linkages between compositional changes in the oral microbiota and their role in mental health among cigarette smokers remain largely unknown. In this study, we used shotgun metagenomics data for the oral microbiome of 105 participants. The data showed Bacteroidota, Fusobacteriota, Firmicutes, Proteobacteria, and Actinobacteria to be the most abundant phyla; Streptococcus, Haemophilus D, and Veillonella are the most abundant genera. Then, we clustered our subjects into avoidance and activation groups based on the behavioral activation for depression scale (BADS). Interestingly, the avoidance group exhibited a higher oral microbiome richness and diversity (alpha diversity). Differential abundance testing between BADS avoidance and activation groups showed the phyla Bacteroidota (effect size 0.5047, q = 0.0037), Campylobacterota (effect size 0.4012, q = 0.0276), Firmicutes A (effect size 0.3646, q = 0.0128), Firmicutes I (effect size 0.3581, q = 0.0268), and Fusobacteriota (effect size 0.6055, q = 0.0018) to be significantly increased in the avoidance group, but Verrucomicrobiota (effect size -0.6544, q = 0.0401), was found to be significantly decreased in the avoidance risk group. Network analysis of the 50 genera displaying the highest variation between both groups identified Campylobacter B, Centipeda, and Veillonella as hub nodes in the avoidance group. In contrast, Haemophilus and Streptococcus were identified as hub nodes in the activation group. Next, we investigated functional profiles of the oral microbiota based on BADS avoidance and activation groups and found Lysine degradations pathway was significantly enriched between both groups (ANCOM-BC, q = 0.0692). Altogether, we provide evidence for the presence of depression-related changes in the oral microbiota of smokers and possible functional contribution. The identified differences provide new information to enrich our understanding of oral microbiota-brain axis interplay and their potential impact on mental health.